How global medium-sized SaaS-companies conduct market intelligence - Pirttijärvi, Heta (My University, 2020)
There is a clear research gap regarding the topic of market intelligence (MI) in global medium- sized SaaS-companies and very limited studies have been made on the matter despite the realized need for market intelligence in such companies. The aim of this thesis is to investigate how global medium-sized SaaS-companies can conduct market intelligence. There are three sub questions in this study: how MI is conducted in general and what factors have an effect on how it is done, what needs to be taken into consideration in MI particularly for medium-sized companies, and what the challenges of conducting MI are for medium-sized SaaS companies. The study is done by first looking into previous studies, focusing on three main models, a structural, attitudinal, and strategic view. Afterwards, a qualitative study is made on the matter with a multiple case study by interviewing five companies. This allows for a broad understanding of the subject as well as the possibility to compare the findings between the companies. The findings of this thesis support previous studies made on similar topics, for example the fact that company size is one of the main factors in determining the level of MI in the company. In addition, the study also brings forth a final framework that shows how global medium-sized SaaS-companies can conduct MI and which factors affect the level of it. In terms of the main findings of the study, one can see three main aspects. Firstly, that global medium-sized SaaS-companies can conduct market intelligence in three main ways, as presented in the final framework. It is, however, argued, whether conducting MI on a higher level would result in a competitive advantage or whether it is necessary or even possible. Secondly, the main aspects that affect the level of MI are company size, internationalization level, importance of MI, level of competition, as well as the people involved in MI. These are factors that managers can consider when pursuing different levels of MI operations. Finally, the largest challenge was found to be the lack of resources available for the operations. In conclusion, the study contributes to theoretical and managerial implications in several ways partly because there are very limited studies on the matter. In addition to supporting previous research, a unique framework is presented to enable for a broad understanding of the topic.